Kualitas hidup terkait kesehatan gigi dan mulut pada anak prasekolah di Batam - Nabillah Rulifa, Syarah; Asia, Asyurati (Jurnal Kedokteran Gigi Terpadu, 2023)
Background: The high number of dental and oral health problems in preschool children, such as dental caries, can indirectly interfere with children's development and daily activities. This situation will affect children's Oral-Health Related Quality of Life (OHRQoL) up to his family. Objective: Defines the quality of life related to dental and oral health at Nabilah Kindergarten in Batam City District. Methods: This research is a descriptive observational study with a cross-sectional design to describe the Oral-Health Related Quality of Life at Nabilah Kindergarten in Batam City District. The research was conducted by distributing ECOHIS questionnaire sheets consisting of 13 question items to 79 mothers of Nabilah Kindergarten students in Batam City District. Respondents filled out the informed consent and ECOHIS questionnaire sheets. The assessment of Oral-Health Related Quality of Life in the questionnaire is divided into four categories, namely good, sufficient, bad, and very bad. The score of each respondent's answer is added up and then adjusted based on the score range of the ECOHIS questionnaire. Results: The results showed that Oral-Health Related Quality of Life in the children impact section was in the good category 68.4%, sufficient 29.1%, bad 2.5%. Meanwhile, the family impact section was 58.2% good, 35.4% sufficient, and 6.3% bad. Conclusion: Oral-Health Related Quality of Life at Nabilah Kindergarten in Batam City District tends to be in the good category.